Selection of a volumetric equation for Eucalyptus urophylla s.t. Blake in the central region of the state of Goiás, Brazil - Imaña-Encinas, José (2019)
es of Eucalyptus urophylla were measured, felled and scaled with the purpose to select a wood volume equation with one and two independent variables. The cross-validation sample was done in 310 trees. The objective of this work was to select and to test tree stem volume equations with one and two independent dendrometrical variables (breast height diameter and height) to be used in a Eucalyptus urophylla plantation at the rotation age for firewood production. Selection criteria were the adjusted coefficient of determination, estimated standard error, graphic distribution of waste and the Furnival index. From seven tested equations with one dendrometrical variable, the Hohenadl-Krenn model (v=ß0+ß1d+ß2d2) showed the highest statistical reliability and it presented the best fit (R2aj = 0.98, Sx = 0.06 e IF = 0.01), producing the regression equation: v = 21.5461 + 4.4448·d + 0.2247·d2. From the other nine volume models that were considered, the two variable Meyer equation (v=ß0+ß1d+ß2d2+ß3dh+ß4d2h+ß5h) presented the best fit, but lower than the Hohenadl-Krenn model.